2017
DOI: 10.1161/circep.117.005591
|View full text |Cite
|
Sign up to set email alerts
|

Localized Optogenetic Targeting of Rotors in Atrial Cardiomyocyte Monolayers

Abstract: Localized optogenetic targeting of rotors in atrial monolayers could lead to both stabilization and destabilization of reentrant activity. For termination, however, a line of block is required reaching from the core region to at least 1 unexcitable boundary. These findings may improve our understanding of the mechanisms involved in rotor-guided ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 30 publications
0
55
0
Order By: Relevance
“…Using a reductionist cell monolayer approach, termination was found to require a line of conduction block reaching from the rotor core to at least 1 unexcitable boundary. 3 In contrast, incomplete conduction block merely provides a stable anchor for rotors to circulate about and perpetuate AF (Figure 1). Thus, providing critical insights into the mechanism(s) underlying procedural success for a novel ablation strategy that, to date, has met with variable outcomes.…”
Section: Atrial Arrhythmiasmentioning
confidence: 99%
“…Using a reductionist cell monolayer approach, termination was found to require a line of conduction block reaching from the rotor core to at least 1 unexcitable boundary. 3 In contrast, incomplete conduction block merely provides a stable anchor for rotors to circulate about and perpetuate AF (Figure 1). Thus, providing critical insights into the mechanism(s) underlying procedural success for a novel ablation strategy that, to date, has met with variable outcomes.…”
Section: Atrial Arrhythmiasmentioning
confidence: 99%
“…a reversible conduction block) near the core of a spiral wave, and (ii) emergence of a wave from the spot of illumination. In a previous study ( Feola et al, 2017 ), we demonstrated the possibility to create such a temporal heterogeneity with optical control over the size, location and duration of the block. Here, we show how creation of a light-induced block close to the core of a spiral wave, can attract the spiral wave tip, causing it to eventually anchor to the block.…”
Section: Resultsmentioning
confidence: 99%
“…While previous studies by Feola et al ( 2017 ) and Majumder et al ( 2018 ) have proven that full spatio-temporal control over the dynamics of a spiral wave can be achieved by manipulating its core with supra-threshold illumination, the efficacy of their respective methods at sub-threshold illumination, remained untested. In this study, we exploited the power of regional sub-threshold illumination, to manipulate spiral wave dynamics with or without prior knowledge about the location of the spiral core.…”
Section: Discussionmentioning
confidence: 99%